CRISES PHENOMENA OF POLITICAL SYSTEM - Шаповаленко, М. В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2018)
The article deals with research tools for solving the key problem of the development of the political system in the context of crisis phenomena. Political institutions in the context of system transformation show their vulnerability to different types of challenges of varying scale and complexity. Therefore, it is important to develop an integrated approach to the analysis of the crisis of the political system. Taking into account the openness and non-linear nature of the political system's development, it is proposed to combine the Stanford model of the crisis of development  and the synergetic approach.